Preparation and Electrochemical Properties of CaZr1-xScxO3-α. Issue 6 (5th April 2019) - Tian, Zhen; Ruan, Fei; Bao, Jinxiao; Song, Xiwen; An, Shengli; Wu, RuMing; Jing, Qiang; Lv, Hao Dong; Zhou, Fen; Xie, Min
Abstract : To develop a CaZrO3 -based, high-temperature proton conductor with high conductivity and resistance to the reduced atmosphere, we used Sc as a substitute for In as the dopant in CaZrO3 . The electrical conductivity of CaZr1- x Sc x O3- α ( x = 0.06, 0.12, 0.18, and 0.24) specimens was measured using the two-terminal ac method in an oxygen-rich atmosphere, hydrogen-rich atmosphere, and water vapor-rich atmosphere, at temperatures ranging from 573 K to 1473 K. The electrical conductivity of the CaZr1- x Sc x O3- α samples first increased and then decreased with the increase in amount of Sc2 O3 doping, and it increased with an increase in temperature. The results of the H/D isotope effect measurement indicated that in the three different atmospheres, at temperatures from 573 K to 1273 K, protons are the dominant charge carrier. From the measurement of electromotive force, the theoretical (calculated) and the measured electromotive forces coincided. The proton mobility of CaZr1- x Sc x O3- α exceeded 90% in the hydrogen-rich atmosphere at temperatures from 573 K to 1273 K. At higher temperatures of 1373 K to 1473 K, positive holes were the dominant charge carrier in the oxygen-rich atmosphere, whereas the dominant charge carrier was vacancies in the hydrogen-rich atmosphere. These results agree with our previous studies.